Digitized thermo-responsive shape memory matrix band for tooth restorations - Chao Liu; Qin Huang; Bin Feng; Guanchen Ye; Yu Wang; Tianer Zhu; Junjie Wu; Lining Lin; Dongqi You; Haiping Yang; Weifang Zhang (Scientific Reports)
Abstract Direct resin restoration has been widely used to restore the tooth defect for its convenience and minimal invasion. However, the accuracy of the final contour of class II restoration is often unpredictable and quite technique-sensitive due to the limitation of traditional matrix band system. In this study, the authors developed a novel matrix band system using shape memory polymer (SMP), which possessed two reversible shapes including digitized permanent shape to reproduce anatomical proximal contour and programmable temporary shape for clinical practice and reservation. The permanent shape could be designed and customized in software or retrieved from imaging database collected from large general population. Only warm saline or water was needed to trigger the shape transformation without any auxiliary tools. The results of in vitro class II restoration showed the shape memory matrix bands brought the best proximal profile and contact point, compared to traditional metal matrix and sectional matrix. The novel shape memory matrix system represents the comfortable, precise, and minimally invasive trend of dentistry and has a broad industrialization prospect as a dental instrument.